Education the Future Engineers - Amca, Hasan (The European University of Lefke, 2012)
[Abstract Not Available]
Prof. Dr. Hasan AMCA was the key-not speaker of the Symposium.
Keywords: Enginnering - Perspectives - World - World in the Future; Engineering Areas; Social Challenges; Different Nations; Engineering Jobs; Cultural Challenges